Effects of growth factors during in vitro culture of mouse and rat embryos - E. Yu. Brusentsev; T. N. Igonina; I. N. Rozhkova; D. S. Ragaeva; S. Ya. Amstislavsky (Вавиловский журнал генетики и селекции)
In vitro culture of preimplantation embryos of ICR, HT1AN/Icgn, HT1AC/Icgn and C57BL/6J-Ay mouse strains as well as in OXYS/Icgn rat strain in media containing granulocyte-macrophage colony stimulating factor (GM-CSF) or epidermal growth factor (EGF) has been studied. Both mouse and rat embryos were first frozen in a programmable freezer after a standard protocol using a mixture of glycerol and sucrose as cryoprotectants, thawed and cultured in vitro in R1ECM (rat one-cell embryo culture medium) for 24 hours (mice) and 72 hours (rats). For the in vitro culture experiments with these growth factors, 8-cell frozen-thawed mouse embryos and 2–4-cell frozen-thawed rat embryos were used. Supplementation of the culture medium with GM-CSF improved the rate of embryonic development in HT1AC/Icgn and C57BL/6J-Ay strain mice, while EGF had no effect. The reverse was true of the rats. Supplementation of the culture medium with EGF increased the percentage of developing blastocysts in OXYS/Icgn rat strain, while GM-CSF had no effect. Co-culture of four-cell embryos of HT1AN/ Icgn strain mice with more advanced embryonic stages (morulas) of a different strain ICR led to the facilitation preimplantation embryo development. Experimental results presented here reveal the species-specific effects of growth factors on mouse and rat embryos and indicate that co-culture of different stages of embryo development have stimulatory effects on earlier stages.